Spatial variations of shear-wave velocity anomaly derived from Love wave ambient noise seismic tomography along Lembang Fault (West Java, Indonesia) - Syaifuddin Firman; Zulfakriza; Nugraha Andri D.; Daryono Mudrik R. (Open Geosciences)
The Lembang Fault, located north of Bandung in West Java, Indonesia, is an active fault that can pose a significant earthquake hazard. The Fault extends 29 km in an east-west direction and is capable of generating earthquakes of magnitude 6.5–7.0 based on surface geological observations and previous paleoseismological studies. In earthquake mitigation, it is crucial to accurately describe the geometry of potential earthquake sources. Therefore, a subsurface model supported by high-resolution data is necessary to adequately characterize the geometry of the Lembang fault. Love wave ambient seismic noise tomography was used in this study to create a seismic velocity model based on data from 74 recording stations. The model accurately characterizes the high velocity contrast and low shear wave velocity anomalies associated with the Lembang Fault Zone. Pronounced velocity anomalies are observed, suggesting that they are related to the fault plane, which is confirmed by seismic activity in the region. In addition, the evidence has been found for another possible fault. Lembang fault has two fault planes: One is a vertical fault and the other is a south-dipping thrust fault. This fault is a cause for concern as it has the potential to generate earthquake with significant consequences.